KORPORATIV BOSHQARUVNING KOMPANIYA KAPITAL QIYMATIGA TA’SIRI (Marketing Journal, 2025)
This article provides an empirical analysis of the impact of corporate governance on capital value . The study examines the effects of the proportion of independent directors, dividend policy, and state ownership on company value . The results indicate that an increase in independent directors and a stable dividend policy enhance company value , while high state ownership negatively impacts it . These findings are compared with international studies , and practical recommendations include improving the corporate governance system, maintaining a stable dividend policy, and increasing management independence in state -owned companies . 256
Keywords: corporate governance; company capital value; independent directors; dividend policy; state ownership; empirical analysis; Uzbekistan market; management independence